Pelaksanaan Pendamping Desa Menurut Permendes - Hasibuan, Ricky Wahyu (Jurnal El-Thawalib, 2022)
Village assistants are tasked with increasing community empowerment in a village, to assist the work of village assistants located at the sub-district level, it is necessary to have local village assistants (PLD) based directly in the village. Then the Regulation of the Minister of Villages, Development of Disadvantaged Regions and Transmigration Number 19 of 2020. This research is an empirical normative research, with data collection carried out by observation and interviews. To ensure the acquisition data, the credibility test, transferability test, depandibility test and confirmability test were carried out, then analyzed using inductive qualitative methods. Implementation of Village Minister Regulation No. 19 of 2020 article 10 paragraph 3 has not been effective because there are still many people who consider village assistants to be irresponsible after construction without any steps to take care of them. A review of siyasa fiqh on the implementation of the Village Minister Regulation No. 19 of 2020 article 10 paragraph 3 regarding the duties of village assistants can be seen from the side of the dusturiyah siyasa, namely the leader should oblige the community to obey and obey the rules that have been set. Factors inhibiting the implementation of the Minister of Village Regulation No. 19 of 2020 article 10 paragraph 3 is the knowledge of village assistants about their duties and responsibilities and many people do not want to know about the duties of village assistants. Factors supporting the implementation of the Minister of Village Regulation No. 19 of 2020 article 10 paragraph 3, among others are: 1) Management of basic social services, utilization of natural resources and appropriate technology, development of village infrastructure, and empowerment of rural communities. 2) Increasing the capacity of the Village Government or village community institutions in the development and empowerment of rural communities. 3) Organizing village community groups. 4) Capacity building for village community empowerment cadres and the creation of new cadres. 5) Assisting villages and communities in the participatory development of rural areas. 6) Coordination of facilitation at the sub-district level and reporting facilities on the implementation of mentoring.